Entre pretérito e presente, entre transformações e permanências: inserção urbana e práticas socioespaciais a partir da Praça Costa Pereira em Vitória/ES, Brasil - Fadini, Michela Sagrillo Pegoretti (2022)
The research presented here starts from the problem that involves the so-called "crisis" of public open spaces and contemporary, intense, and diversified appropriations observed in Costa Pereira square in downtown Vitória, a city located in southeastern Brazil. Using the condition of the square as a colonial square formed by the precepts of Portuguese urbanism, that maintains a strong relationship with the physical site, the general objective of the thesis is to verify the participation of urban insertion and socio-spatial practices in Costa Pereira square, from the main transformations that have taken place In the transition of the 19th and 20th centuries, examining the condition of the liveliness of the place in the face of the argument of the fragility of public spaces in contemporary times. In order to do so, the field of Historical Geography and Urban Morphology is used as investigative possibilities in an inductive methodological approach that brings together bibliographic, documentary and case study research. While the observations in the present are based on field visits, the past is reached by examining periodicals from the Digital Hemeroteca of the National Library and studies on the urban form from four morphological elements: physical site, road, square, and a single building. The results show that even in the face of tissue overlaps and inversion of cultural values when the colonial square became a garden square, there is a sense of embryonic centrality that dialogues with the resilient behavior of form, supporting the permanence in which certain past practices arrived to the present subsidized by an urban insertion conceived in a strategic way